PRAKTIK POLITIK TATA RUANG DI KABUPATEN TUBAN DALAM PROSES INDUSTRIALISASI - Bayu Priambodo; Muhammad Chabibi (Universitas Airlangga, 2021)
Spatial planning has only been seen as an effort to meet development growth and only focuses on economic development. However spatial planning should not only focus on the economic sector but should also pay attention to other crucial sectors. This indicates that it does not take into account the zoning and purpose of spatialisation. This study attempts to look at ow the spatial planning process in Tuban Regency is undergoing a process of industrialization because many large factories are relocating to the Tuban area. The relocation of the factory to the Tuban area has increased the practice of spatial planning politics. The practice of spatial planning politics in Tuban Regency in this study is analyzed using Lefebvre's point of view which states that there are three parties to spatial planning. The method in this study is qualitative and the data collection technique uses the interview method. The results of this research show that the practice of space can be seen from how the government, the private sector and the community collaborate with each other to provide space so that industrialization can run. Many large factories are starting to be built in the Tuban area. The representation of space can be seen from how the government of Tuban Regency plans the arrangement so that there is an even distribution in each region. The northern and western regions are more focused on industrialization. The southern region is more focused on agricultural areas. the central region is focused on the center of government and trade and for the east it is focused on tourist attractions. The third is the representation space where this can be seen from how the government of Tuban Regency makes efforts to control the conversion of agricultural land for food. This is done because every year the agricultural land in Tuban Regency is decreasing so it needs to be maintained to maintain food security.